Kidspreneur initiation through making prayer mats with quilting techniques at Aisyiyah Orphanage Karanganyar - An Nurrahmawati; Khresna Bayu Sangka; Dian Perwitasari; Estetika Mutiaranisa Kurniawati; Nur Chayati; Saktiana Rizki Endiramurti; Bagas Narendra Parahita; Lies Nurhaini (Community Empowerment, 2022)
Mentally and financially independence are essential matters that should be learned early. Among them are for children who do not have guardians or parents. Solutions designed to encourage independence, by teaching additional skills and instilling an entrepreneurial mentality in children or Kidspreneurs. The team chose to train sewing skills using the quilting technique because it is basic and easy, and the raw materials are inexpensive and readily available. The program focused on making prayer mats considering the simple shape and the uneven age and sewing skills of the children. In addition to providing entrepreneurial mental strengthening and sewing training on quilting techniques, the team also provided assistance with sewing machines, patchwork and sewing tools. The results of the training show the enthusiasm of the children and their desire to become entrepreneurs. From this training, the children of Aisyiyah Karanganyar orphanage members will be able to be independent and even contribute to similar empowerment in their surroundings.